Dermatoscopic and histopathological features of dermatofibromas - Kh.M. Khachikyan; A.P. Topchyan; A.D. Getman (Russian Journal of Clinical Dermatology and Venereology, 2026)
Dermatofibroma (DF) is one of the most common benign skin neoplasms of fibrohistiocytic origin. The modern understanding of clinical manifestations, histopathological types, as well as dermatoscopic features and patterns of DF is discussed. Special attention is given to the importance of differential diagnosis with other skin tumors, including malignant neoplasms. The main morphological features of DF include localized proliferation of spindle-shaped fibroblast-like and histiocytoid cells in the dermis, the presence of randomly arranged coarse collagen fibers, increased angiogenesis, and the occurence of an inflammatory infiltrate. The following main histopathological types of dermatofibroma are distinguished: fibrocollagenous, sclerotic, cellular, histiocytoid, atypical, lichenoid, keloid, lipidized, hemosiderotic/aneurysmal, epithelioid and atrophic. The classic dermatoscopic features of DF, most frequently occurring in this formation, include a peripheral delicate pigment network and a central white zone. Additional dermatoscopic features include vascular structures, homogeneous pigmentation, globule-like elements, white streaks, ring-shaped or donut-shaped structures, brown streaks, areas of ulceration, and comedo-like structures. A model with pigment network and a model without pigment network are typical dermatoscopic models. There are also DFs that, based on their dermatoscopic symptoms, do not belong to any of the above mentioned models and are called alternative DF models.